A Practicum in Behavioral Economics - Caplan, Arthur J (Open textbook library.)
A Practicum in Behavioral Economics is a practice-based textbook covering the broad field of behavioral economics. Because behavioral economics is foremost a “test-and-learn” field of scientific inquiry that evolves according to experimental outcomes, so too should students test-and-learn. As such, the book’s primary goal is to help students experience behavioral economics through participation in the same experiments and games that serve as the foundations for, and shape the contours of, the field. With the help of this book students learn behavioral economics firsthand, and in the process create their own experiences. They learn about themselves – about how they make private and public choices under experimental conditions – at the same time as they learn about the field of behavioral economics itself.